Restoration of Livestock Services in Conflict and Drought Affected areas of Ethiopia (RESTORE): Gender analysis tools - Lemma, Mamusha; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
This document presents gender analysis tools designed to support the Restoration of Livestock Services in Conflict and Drought Affected areas of Ethiopia (RESTORE) project in understanding and addressing gender dynamics in animal health and feed services across Tigray, Afar, and South Ethiopia. It provides structured field guides for conducting focus group discussions (FGDs) with women-only and men-only community groups, as well as key informant interviews (KIIs) with veterinary and feed sector officials. The tools are intended to identify gender-based differences in roles, responsibilities, access, control, needs, and challenges in livestock management, especially in animal healthcare and feed systems. They also examine institutional mechanisms for gender mainstreaming, highlight barriers and opportunities for gender-responsive service delivery, and propose actionable entry points for more inclusive programming. Supporting annexes offer detailed guidance on facilitation, sampling, and note-taking to ensure high-quality data collection and analysis. To ensure effective use of these tools, RESTORE project partners will receive gender training that covers key frameworks, methods, and practical exercises using the tools. Following the training, partners will carry out gender analysis in their intervention areas and facilitate structured reflections to validate findings and identify key themes. These insights will be shared within partner institutions to raise awareness and foster institutional engagement. Trained individuals will act as focal points, leading and supporting the integration of gender considerations into project planning, implementation, and reporting.